(untitled) (World Bulletin of Public Health, 2023)
Systemic scleroderma is a multisystemic disease involving skin and internal organs (gastrointestinal tract, lungs, heart, kidneys, and peripheral nervous system). The pathogenesis of the disease includes dysfunction of the endothelium, epithelium, fibroblasts, as well as activation of the immune system and inflammatory mediators. In addition, the disease is characterized by impaired angiogenesis. Vasculopathy is the basis of pulmonary arterial hypertension, renal pathology, and digital ulcers. This article is devoted to a review of the diagnosis of systemic scleroderma, consideration of its secondary preventive criteria and approaches to treatment from the point of view of evidence-based medicine. This article provides an overview of the results of scientific research on the problem of systemic scleroderma over the past 10- 15 years.